2019
DOI: 10.1080/03009742.2019.1577490
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan concentration and molecular mass in psoriatic arthritis: biomarkers of disease severity, resistance to treatment, and outcome

Abstract: Objective: Low molecular mass hyaluronan causes inflammatory processes and can act as a pro-inflammatory cytokine in skin and other sites of activity in psoriatic arthritis (PsA). This study investigated whether the molecular mass distribution of hyaluronan (HA) in skin and the quantity of circulating HA are related to the clinical inflammatory picture in PsA with active disease and to the effect of treatment with anti-tumour necrosis factor-α (anti-TNF-α) adalimumab. Methods: Twenty patients with TNF-α-naïve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…measured skin inflammation, serum hyaluronan (HA) and molecular mass of HA in patients subsequently treated with adalimumab. 47 Patients with elevated HA values had more retained swollen joints and higher overall disease activity after 12 weeks of treatment. Muramatsu et al .…”
Section: Resultsmentioning
confidence: 93%
“…measured skin inflammation, serum hyaluronan (HA) and molecular mass of HA in patients subsequently treated with adalimumab. 47 Patients with elevated HA values had more retained swollen joints and higher overall disease activity after 12 weeks of treatment. Muramatsu et al .…”
Section: Resultsmentioning
confidence: 93%
“…The reduced generation of butyrate in psoriasis patients may compromise the integrity of the intestinal epithelial barrier, resulting in immune responses and chronic inflammation (Bischoff et al, 2014;Christensen et al, 2018;Shapiro et al, 2019). It has been reported that hyaluronan can act as a pro-inflammatory cytokine and induce inflammatory processes in psoriatic arthritis (Hellman et al, 2019). The VEGF signaling pathway plays an important role in psoriasis, and modified hemicellulose suppresses VEGF-induced angiogenesis (Malecic and Young, 2016;Zhu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Several possible mechanisms have been suggested to be involved in the aetiology, disease expression, and prognosis of PsA, such as different genetic and environmental factors. Other mechanisms have also been of interest; for example, hyaluronan expression seems to be a possible factor in the inflammatory pathology of PsA acting as a biomarker for disease severity, resistance to treatment, and worse outcome (7). The present study focuses on genes related to inflammasomes.…”
mentioning
confidence: 99%